GPT-4 for Developers - Campesato, Oswald (MLI Generative AI Series, 2024)
Extensive Python 3.x code samples generated using ChatGPT and GPT-4, covering diverse programming tasks and challenges. Comprehensive exploration of data visualization techniques using popular Python libraries such as Matplotlib and Seaborn. This resource is designed to bridge the gap between theoretical understanding and practical application, making it a useful tool for software developers, data scientists, AI researchers, and tech enthusiasts interested in harnessing the power of GPT-4 in Python environments. The book contains an assortment of Python 3.x code samples that were generated by ChatGPT and GPT-4. Chapter 1 provides an overview of ChatGPT and GPT-4, followed by a chapter which contains Python 3.x code samples for solving various programming tasks in Python. Chapter 3 contains code samples for data visualization, and Chapter 4 contains code samples for linear regression. The final chapter covers visualization with Gen AI (Generative AI) and DALL-E. Companion files with source code and figures are available for downloading.